Proceedings of the Thirty-First International Joint Conference on Artificial Intelligence 2022
DOI: 10.24963/ijcai.2022/141
|View full text |Cite
|
Sign up to set email alerts
|

Robustifying Vision Transformer without Retraining from Scratch by Test-Time Class-Conditional Feature Alignment

Abstract: Spatial representation capable of learning a myriad of environmental features is a significant challenge for natural spatial understanding of mobile AI agents. Deep generative models have the potential of discovering rich representations of observed 3D scenes. However, previous approaches have been mainly evaluated on simple environments, or focused only on high-resolution rendering of small-scale scenes, hampering generalization of the representations to various spatial variability. To address this, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
(9 reference statements)
0
12
0
Order By: Relevance
“…Test-time entropy minimization (Tent) [16] adapts to the target unlabelled online data by minimizing the Shannon entropy [25] of its prediction by updating only the affine transformation parameters of batch normalization. Tent was proven to be effective when the model is CNN that has batch normalization, e.g., ResNet50 [26], while recent study [17] has demonstrated that Tent is also applicable to ViT (see Sect. 3.1 for the details).…”
Section: Test-time Adaptationmentioning
confidence: 99%
See 4 more Smart Citations
“…Test-time entropy minimization (Tent) [16] adapts to the target unlabelled online data by minimizing the Shannon entropy [25] of its prediction by updating only the affine transformation parameters of batch normalization. Tent was proven to be effective when the model is CNN that has batch normalization, e.g., ResNet50 [26], while recent study [17] has demonstrated that Tent is also applicable to ViT (see Sect. 3.1 for the details).…”
Section: Test-time Adaptationmentioning
confidence: 99%
“…3.1 for the details). One can also use different loss functions for updating parameters, such as pseudo-label (PL) [27], diversity regularization (SHOT-IM) [28], feature alignment (TFA [29] and CFA [17]), or contrastive learning [30]. A recent study of Iwasawa et al [31] has proposed gradient-free procedures to update only the classifier parameter of model (T3A).…”
Section: Test-time Adaptationmentioning
confidence: 99%
See 3 more Smart Citations